Progression Free Survival pada Pasien Kanker Paru Adenokarsinoma Wild Type dengan Kombinasi Regimen Pemetrexed dengan Cisplatin dibandingkan dengan Karboplatin - Agus Setyawan, Ungky; Purnamawati, Catur; Pratiwi, Suryanti (Jurnal Klinik dan Riset Kesehatan, 2025)
Background: Progression-free survival (PFS) is a parameter to measures the progression of wild type adenocarcinoma lung cancer. Literature studies have shown that the combination platinum based-pemetrexed chemotherapy is more effective to prolonged progressivity of wild type adenocarcinoma. Aim: The aim of study to compared the PSF of wild type adenocarcinoma patients receiving cisplatin-pemetrexed and pemetrexed-carboplatin regimens at Dr. Saiful Anwar Hospital in 2018-2021. Methods: A retrospective cohort study based on medical record of wild type adenocarcinoma patients. Results: The results showed that the administration of a carboplatin-pemetrexed regimen has prolonged PFS (median 4 months, 95% CI 2.657-5.343) compared to the cisplatin-pemetrexed regimen (median 2 months, 95% CI 0.988-3.012). In addition, the risk of lung cancer progression based on PFS is not significantly influenced by the Karnofsky scale value of 70-80 (72.2%, HR 0.278). On the other hand, a history of smoking increases the risk of lung cancer progression, although it does not have a significant effect (HR 1,538). Conclusion: Administration of the carboplatin-pemetrexed regimen prolongs PFS up to a range of 10-16 months, although there is no statistically significant difference compared to the cisplatin-pemetrexed.